Smoothing control of wind generator output fluctuations by PWM voltage source converter and chopper controlled SMES - Sheikh, M.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2011)
Since the mechanical power extracted from wind is proportional to the cube of the wind speed, the output of the wind turbine generator system fluctuates considerably due to wind speed variations. Therefore, high penetration of wind power to the power grid causes fluctuation of the grid frequency, which has adverse effects on power system stability and reliability. Since a superconducting magnetic energy storage (SMES) system has the ability to provide both active and reactive power simultaneously and quickly, the SMES system can be an effective tool to mitigate frequency fluctuations under such conditions. In the present study, a PWM voltage source converter and two-quadrant DC-DC-chopper-controlled SMES system is proposed, which can significantly decrease the voltage and output power fluctuations of the wind farm and consequently mitigate the grid frequency fluctuation. A computational method by which to determine the SMES power rating needed to minimize the grid frequency fluctuation is analyzed. Moreover, the required minimum energy storage capacity of the SMES unit is determined. The simulation analyses were performed using PSCAD/EMTDC.